One Monday morning - Shulevitz, Uri (New York : Scholastic Inc, 1967)
One Monday morning the King, the Queen, and the little prince go to visit a friend. But he's not home. What day of the week do they finally get to see each other?
Keywords: Days of the week-Fiction; Children's stories-Fiction